A Profile Of Patients Registered At Art Centre At Surat Municipal Institute Of Medical Education & Research In Surat City, Gujarat, India (SAARC Journal of Tuberculosis, Lung Diseases and HIV/AIDS, 2012)
Introduction: An estimated 2.4 million Indians are currently living with HIV. In India, the antiretroviral treatment program started with a free ART treatment in 2003. This study was conducted in order to understand the clinico-epidemiological profi le of patients attending ART centre and the effectiveness of the therapy. Methodology: A cross sectional study was conducted at an ART center of Surat Municipal Institute of Medical Education and Research (SMIMER), in Surat city of Gujarat State. The data of 2357 PLHAs (People Living with HIV/ AIDS) registered at ART centre in one year time duration starting from 21st January 2010 was included in the study. Results: Among the total 2357 subjects, 1483 (63%) were males. In our study 42.3% of patients were between 31 to 40 years of age. Among the employed subjects, 32.9% of patients were laborer. Voluntary Counseling and Testing Centre (VCTC) was most common entry point of patient with 50% followed by private practitioner with 23% and NGOs with 6.2%. Other entry points are self referred, RNTCP etc. Tuberculosis and diarrhoea were the most common opportunistic infections. There was signifi cant improvement in CD4 count, bodyweight and functional status of the subjects after receiving the ART for an average duration of 6 months. Conclusion: The economically productive & sexually active people and those with lesser education are at higher risk of becoming sero-positive. The subjects showed signifi cant improvement after receiving ART with respect to the CD4 count and average body weight. DOI: http://dx.doi.org/10.3126/saarctb.v8i2.5895 SAARCTB 2011; 8(2): 11-16